2021
DOI: 10.1063/5.0073728
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic analysis of fish schools arranged in the vertical plane

Abstract: Schools of fish can provide individuals with hydrodynamic advantages, thereby improving the swimming efficiency. Fish schools in nature are mostly spatial configurations, not just limited to the horizontal plane. Through three-dimensional numerical simulations, this paper discusses the hydrodynamic characteristics and flow field structure of fish schools in various vertical patterns. The results show that a school of fish arranged vertically can improve the thrust and swimming efficiency of individuals as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Similarly, Oza et al (2019) observed that a 2D rectangular lattice formation offers the largest hydrodynamic benefit when compared to in-line, phalanx, and solitary swimmers. The results from these studies suggest that the combined utilization of the channeling effect and wake energy can achieve higher efficiency (Li et al 2021c).…”
Section: Major Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Similarly, Oza et al (2019) observed that a 2D rectangular lattice formation offers the largest hydrodynamic benefit when compared to in-line, phalanx, and solitary swimmers. The results from these studies suggest that the combined utilization of the channeling effect and wake energy can achieve higher efficiency (Li et al 2021c).…”
Section: Major Resultsmentioning
confidence: 90%
“…Altering the schooling configuration into a rectangular/square or diamond configuration will alter the resulting hydrodynamic impacts. Studies using this configuration generally saw an increase in thrust and propulsive efficiency (Li et al 2021c) compared to a single fish. Daghooghi and Borazjani (2015) found that an individual fish in this schooling configuration could achieve up to a 20% higher cruising speed than a sole swimmer.…”
Section: Major Resultsmentioning
confidence: 99%
See 3 more Smart Citations